2014
DOI: 10.1680/geot.13.t.033
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of clay-fouled ballast under cyclic loading

Abstract: Expansion of the rail network in congested coastal Australia compels track construction on soft clayey subgrade, including fine-grained estuarine soils. In such low-lying areas, where the water table is close to the ground surface, the saturated soft subgrade is often subjected to pumping (mud slurry) under the application of cyclic wheel loads, thereby causing fouling of the overlying ballast. This technical note presents the results of a series of large-scale, drained, cyclic, triaxial tests conducted on cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 18 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…On the other hand, subsequent studies (Alobaidi and Hoare 1996;Muramoto et al 2006;Duong et al 2014;Chawla and Shahu 2016) proposed the existence of an apparent relationship between the rising EPP and the vulnerability of fines for infiltrating the upper granular layers. The process of fluidized fines transported upwards from the soil (subgrade) often results in the fouling of overlying ballast causing a reduction in the inter-particle friction (shear strength) and impeding the drainage capacity (permeability) of the granular assembly (Selig and Waters 1994;Ionescu 2004; Tennakoon and Indraratna 2014). In order to reduce maintenance and enhance the longevity of ballasted tracks, the cyclic response of EPP and undrained strains in relation to this fluidization process must be addressed (Indraratna et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, subsequent studies (Alobaidi and Hoare 1996;Muramoto et al 2006;Duong et al 2014;Chawla and Shahu 2016) proposed the existence of an apparent relationship between the rising EPP and the vulnerability of fines for infiltrating the upper granular layers. The process of fluidized fines transported upwards from the soil (subgrade) often results in the fouling of overlying ballast causing a reduction in the inter-particle friction (shear strength) and impeding the drainage capacity (permeability) of the granular assembly (Selig and Waters 1994;Ionescu 2004; Tennakoon and Indraratna 2014). In order to reduce maintenance and enhance the longevity of ballasted tracks, the cyclic response of EPP and undrained strains in relation to this fluidization process must be addressed (Indraratna et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To understand how mud pumping affects the resilient modulus (M r ) of ballast [10], a series of cyclic tests were carried out using the large-scale model, as shown in Fig. 14.…”
Section: Degraded Resilient Modulusmentioning
confidence: 99%
“…Ballast fouling generally has three sources: (1) ballast abrasion and breakage, (2) external sources such as coal waste and dust, and (3) subgrade fluidisation and infiltration through the subballast and ballast layers. While the mechanism of types (1) and (2) has already been addressed to some degree [8][9][10], existing studies on the fouling mechanism induced by subgrade fluidisation are limited. The following paper addresses the mechanism of subgrade fluidisation induced by high cyclic stresses induced by the railway loading through a series of undrained cyclic triaxial tests.…”
Section: Introductionmentioning
confidence: 99%
“…Without appropriate drainage, cyclic loading can cause undrained shear failure of the soft subgrade and also induce localised 'mud pumping' that will result to a serious loss of stiffness and fouling of the track. Ballast mixed with pumped-up mud fines (fouled ballast) can result in excessive deformation and localised failure under undrained condition due to the reduction of its overall drainage properties, shear strength and resilient modulus (Tennakoon & Indraratna 2014). found that when the fouling index exceeds 30%, the drainage capacity of the track can be insufficient considering a significant rainfall event (>67.5 mm/hour).…”
Section: Introductionmentioning
confidence: 99%